The “Sanitary” Role of the Necrophagous Birds in the Ecosystems - Karimov Tahir; Ahmadli Leyla; Rajabova Sevinj; Mammadov Ayaz (BIO Web of Conferences)
The objective of the research work was to study the “sanitary” role of necrophagous birds (Gyps fulvus, Aegypius monachus, Gypaetus barbatus, Neophron percnopterus) in the Azerbaijani part of the Lesser Caucasus. For this purpose, monitoring was conducted in the Korchay State Nature Reserve and adjacent territories in June 2013. During this period, we identified carcasses of animals that had died from various causes, including those carrying infectious diseases. In total, 28 carcasses of domestic (n=5) and wild (n=5) mammals were found. Among these, 13 carcasses were associated with six infectious diseases: rabies (five cases), toxoplasmosis (one case), brucellosis (two cases), equine adenitis (two cases), tuberculosis (one case), and canine disease (two cases). Echinococcus was identified in four animals. Notably, the number of sick animals included eight domestic and nine wild specimens. The primary causes of death for sick domestic animals were predation by mammals in pastures, old age, weakness, and hunger. Among wild animals, mortality was predominantly observed in young individuals, attributed to their inexperience and underdeveloped adaptive responses, which led them to venture into populated areas for food, making them vulnerable to hunting, traps, and transportation hazards.